# Tensor Analysis & Geometry

Spherical Coordinates x1 = r sin θ cos φ , x 2 = r sin θ sin φ , x 3 = r cosθ , x 4 = ct
3-dimensional line element:

ds 2 = dr 2 + r 2 dθ 2 + sin 2 θdφ 2

(

)

Christoffel Symbols
Christoffel Symbol of the first kind: Christoffel Symbol of the second kind:

Γrmn = [mn, r ] =

1  ∂g rm ∂g rn ∂g mn + m −  2  ∂x n ∂x ∂x r

 . 

z Γmn =  z  = g rz Γmnr . mn 

Derivation of the Riemann Curvature Tensor
In general, a second order differentiation on a covariant vector is independent of the order in which it is carried out, i.e.:

∂ 2Vi ∂ 2V = k ij . ∂x j ∂x k ∂x ∂x
However, the presence of Christoffel symbols can have an effect on this statement. We investigate this by first finding the general second derivatives for both permutations of the differentiating parameters:

(V )
k

i ; j ;k

r r = Vi , jk − Γik Vr , j − Γ jk Vi ,r .

But

Vi ; j = Vi , j − ΓijsVs , ∴ (Vi: j ):k = Vi , jk − ⇔ (Vi: j ):k = Vi , jk − ∂Γijs ∂x ∂Γijs ∂x
k r s r s Vs − ΓijsVs ,k − Γik Vr , j − ΓrjVs − Γ jk Vi ,r − Γir Vs

[

]

[

]

r r s r r s Vs − ΓijsVs ,k − Γik Vr , j + Γik ΓrjVs − Γ jk Vi , r + Γ jk Γir Vs

Now we interchange j and k (which is the other possible way of determining this second derivative):

(Vi:k ): j

= Vi ,kj

s ∂Γik s s r r s − j Vs − Γik Vs , j − ΓijrVr ,k + Γijr Γrk Vs − ΓkjVi ,r + Γkj ΓirVs . ∂x

We now find the difference between these two. On the RHS, the first, third, fourth, sixth, and seventh terms cancel out, thus giving the result:

Vi: jk − Vi:kj = −

 ∂Γ s ∂Γ s  ∂Γijs ∂Γ s r s s r s s Vs + Γik ΓrjVs + ik Vs − Γijr ΓrkVs =  ik − ij + Γik Γrj − Γijr Γrk Vs . k j j k ∂x ∂x ∂x  ∂x   
s ijk

We define the Riemann (or Riemann-Christoffel) Curvature tensor by:
s s ∂Γik ∂Γij r s s R = − + Γik Γrj − Γijr Γrk . ∂x j ∂x k s The difference between the covariant derivatives can thus be written as Vi: jk − Vi:kj = Rijk Vs . The Riemann

tensor used in this equation is called the Riemann curvature tensor of the second kind. The curvature tensor of the first kind is defined as:

Rijkl = g ir R r . jkl
Symmetry Properties: First skew symmetry Second skew symmetry

Rijkl = − R jikl Rijkl = − Rijlk

Courtney James Mewton

Page 1

GR, Tensor Analysis & Geometry

GENERAL RELATIVITY, TENSOR ANALYSIS AND GEOMETRY

Block symmetry Bianchi’s identity

Rijkl = Rklij Rijkl + Riklj + Riljk = 0

The Ricci Tensor
The Ricci tensor of the first kind is simply a contraction of the Riemann tensor:
k Rij = Rijk .

The last index can be raised to yield the Ricci tensor of the second kind:

Ri j = g ik Rki .
If this tensor is finally contracted by letting I = j, we get the Ricci curvature scalar. If it is zero, the space is flat. From the first of the two equations above the Ricci tensor of the first kind can be calculated directly by:
k Rij = Rijk = k k ∂Γik ∂Γij r k k − k + Γik Γrj − Γijr Γrk . j ∂x ∂x

Transformation Of A Geodesic From Parameter u To v, Where v = f(u)
Given a particular geodesic in terms of a parameter u, in this section the geodesic equation will be transformed so that it is in terms of a new parameter v.

D  dx a  Start with du  du  dx a du D  ∂x a  then du  ∂v 
Substitute

b c  d 2 xa a dx dx =  du 2 + Γbc du du = 0 .  dx a dv = , dv du b c ∂x a d 2 v dv  ∂x a dv a ∂x dv dx = + Γbc + =0 du  ∂u∂v du ∂v du du ∂v du 2  b c dv ∂x a d 2 v a ∂x dx dv + Γbc =− du ∂v du du ∂v du 2 b c dv  du du  ∂x a d 2 v  du du  a ∂x dx dv  du du    + Γbc  =−   du  dv dv  ∂v du du  dv dv  ∂v du 2  dv dv  2

∂x a ⇔ ∂u∂v ∂x a ⇔ ∂u∂v

b c ∂x a ∂x a d 2 v  du  a ∂x dx ⇔ 2 + Γbc =−   . ∂v dv ∂v du 2  dv  ∂v

Since the LHS is now in terms of v, partial differentiation can be replaced by normal differentiation:
b c dx a dx a d 2 v a dx dx ⇔ 2 + Γbc =− dv dv dv du 2 dv

 dv    .  du 

2

By letting

λ=−

d 2v du 2

 dv    , we arrive at the final equation:  du  b c dx a dx a a dx dx + Γbc =λ . dv dv dv dv 2

2

General Relativity
The Metric Tensor for Special Relativity

Courtney James Mewton

Page 2

GR, Tensor Analysis & Geometry

GENERAL RELATIVITY, TENSOR ANALYSIS AND GEOMETRY

η µν

0 0 1 0 0 − 1 0 0  . = 0 0 − 1 0  0 0 0 − 1  

Einstein's Law of Gravitation
Simply stated, Einstein's law of gravitation is: Rµν = 0 . This condition holds when the local space is completely devoid of all forms of matter and energy.

Derivation of the Schwarzchild Solution
In this section the line-element solution to the field equations for a quasi-static gravitational field produced by a spherical body will be derived. We start by setting up a general line element employing spherical coordinates:

c 2 dτ 2 = Ac 2 dt 2 − Bdr 2 − Wr 2 dθ 2 + sin 2 θdφ 2 .
Before we continue, a few assumptions need to be made: The space is asymptotically flat. This means that A = B → 1 as r → ∞ . The gravitational field only affects time and radial distance, so W = 1.

(

)

We can immediately define the metric tensor:

g 00 = Ac 2 , g11 = − B , g 22 = − r 2 and g 33 = − r 2 sin 2 θ .
Since we are dealing with the empty space surrounding the body, the Ricci tensor needs to equal zero. With this in mind, the derivation begins. We first calculate the Christoffel symbols. Note that since a Christoffel symbol of the second kind is defined as
z Γmn =  z  = g rz Γmnr mn 

we need only calculate them for values when r = z.

0 Γ10 = g 00 Γ100 = 1 A −1c −2 [g 00,1 + g10 , 0 − g10, 0 ] = 1 A −1 A′ 2 2

1 Γ00 = g 11Γ001 = − 1 B −1 [g 10 ,0 + g 01, 0 − g 00,1 ] = 1 B −1 g 00,1 = 1 B −1 A′c 2 2 2 2 1 Γ11 = g 11Γ111 = − 1 B −1 [g11,1 + g 11,1 − g11,1 ] = − 1 B −1 g 11,1 = 1 B −1 B ′ 2 2 2 1 Γ22 = g 11Γ221 = − 1 B −1 [g12 , 2 + g 21, 2 − g 22 ,1 ] = − 1 B −1 g 22,1 = − 1 B −1 ⋅ (2r ) = − rB −1 2 2 2 2 Γ21 = g 22 Γ212 = − 1 r −2 [g 21, 2 + g 22,1 − g 21, 2 ] = − 1 r −2 ⋅ (− 2r ) = r −1 2 2

1 Γ33 = g 11Γ331 = − 1 B −1 [g13,3 + g 31,3 − g 33,1 ] = − 1 B −1 (− g 33,1 ) = − 1 B −1 2r sin 2 θ = − rB −1 sin 2 θ 2 2 2 2 Γ33 = g 22 Γ332 = − 1 r −2 [g 23,3 + g 32,3 − g 33, 2 ] = − 1 r −2 ⋅ 2r 2 cosθ sin θ = − cosθ sin θ 2 2

(

)

3 Γ13 = g 33 Γ133 = − 1 r −2 sin −2 θ [g 33,1 + g13,3 − g 13,3 ] = − 1 r −2 sin −2 θ ⋅ − 2r sin 2 θ = r −1 2 2 3 23 33 −2 −2 −2 −2

Γ = g Γ233 = − 1 r sin θ [g 33, 2 + g 23,3 − g 23,3 ] = − 1 r sin θ ⋅ − 2r cosθ sin θ = cot θ 2 2
2

(

(

)

)

We now solve the field equations:

[ + [Γ + [Γ

0 0 0 0 0 0 1 0 1 0 2 0 2 0 3 0 3 0 R00 = Γ00,0 − Γ00 ,0 + Γ00 Γ00 − Γ00 Γ00 + Γ00 Γ10 − Γ00 Γ10 + Γ00 Γ20 − Γ00 Γ20 + Γ00 Γ30 − Γ00 Γ30

[

1 1 0 1 0 1 1 1 1 1 2 1 2 1 3 1 3 1 + Γ01, 0 − Γ00,1 + Γ01 Γ00 − Γ00 Γ01 + Γ01 Γ10 − Γ00 Γ11 + Γ01Γ20 − Γ00 Γ21 + Γ01Γ30 − Γ00 Γ31 2 02 , 0 3 03, 0 2 0 2 0 2 1 2 1 2 2 2 − Γ00 , 2 + Γ02 Γ00 − Γ00 Γ02 + Γ02 Γ10 − Γ00 Γ12 + Γ02 Γ20 3 − Γ00,3 0 03 3 0 3 Γ00 − Γ00 Γ03 1 3 03 10 1 3 Γ − Γ00 Γ13 2 03 3 20

( + (Γ

(

(

)(

) (

) ( )+ (Γ

)

)( )+ (Γ Γ

(

) (

) ( − Γ Γ ) + (Γ Γ − Γ Γ ) + (Γ Γ
2 00 2 22 3 02 2 00 3 23 3 03

) (

)]

)]

2 30

3 2 − Γ00 Γ32 3 3 − Γ00 Γ33

3 30

)] )]

Courtney James Mewton

Page 3

GR, Tensor Analysis & Geometry

GENERAL RELATIVITY, TENSOR ANALYSIS AND GEOMETRY

0 0 0 0 0 0 1 0 1 0 2 0 2 0 3 0 3 0 R11 = Γ10,1 − Γ11,0 + Γ10 Γ01 − Γ11Γ00 + Γ10 Γ11 − Γ11Γ10 + Γ10 Γ21 − Γ11Γ20 + Γ10 Γ31 − Γ11Γ30   1 1 0 1 0 1 1 1 1 1 2 1 2 1 3 1 3 1 + Γ11,1 − Γ11,1 + Γ11Γ01 − Γ11 Γ01 + Γ11Γ11 − Γ11Γ11 + Γ11Γ21 − Γ11 Γ21 + Γ11Γ31 − Γ11 Γ31 2 2 0 2 0 + Γ12,1 − Γ11, 2 + Γ12 Γ01 − Γ11   3 13,1 3 11, 3 0 13 3 01 0 11

)( Γ −Γ + Γ − Γ + (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )]   R = [Γ − Γ + (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )] + [Γ − Γ + (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ )] + [Γ − Γ + (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )] + [Γ − Γ + (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )] R = [Γ − Γ + (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )] + [Γ − Γ + (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )] + [Γ − Γ + (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )+ (Γ Γ − Γ Γ ) + (Γ Γ − Γ Γ )]
(
2 02 1 2 12 11 1 2 2 2 2 Γ − Γ11Γ12 + Γ12 Γ21 − Γ11 1 3 11 13 2 13 3 21 2 11 2 22 3 12 2 31 3 2 11 32 3 03 1 3 13 11 3 23 3 13 3 31 3 3 11 33 22 0 20 , 2 0 22 , 0 0 20 0 02 0 22 0 00 1 20 0 12 1 0 22 10 2 20 0 22 2 22 0 20 3 20 0 32 3 22 0 30 1 21, 2 1 22 ,1 0 21 1 02 0 22 1 01 1 1 21 12 1 1 22 11 2 21 1 22 2 22 1 21 3 21 1 32 3 22 1 31 2 22 , 2 3 23, 2 2 22 , 2 0 22 2 02 0 22 2 02 1 2 22 12 1 2 22 12 2 22 2 22 2 22 2 22 3 22 2 32 3 22 2 32 3 22 , 3 0 23 3 02 0 22 3 03 1 3 23 12 1 3 22 13 2 23 3 22 2 22 3 23 3 23 3 32 3 22 3 33 33 0 30 , 3 0 33, 0 0 30 0 03 0 33 0 00 1 0 30 13 1 0 33 10 2 30 0 23 2 33 2 33 0 20 3 30 0 33 3 33 0 30 1 31, 3 1 33,1 0 31 1 03 0 33 1 01 1 1 31 13 1 32 1 1 33 11 2 31 1 23 1 21 3 1 31 33 3 32 3 33 1 31 2 32 , 3 2 33, 2 0 32 2 03 0 33 2 02 2 13 1 2 33 12 2 32 2 23 2 33 2 22 2 33 3 33 2 32 3 3 0 3 0 3 1 3 1 3 2 3 2 3 3 3 3 3 + Γ33,3 − Γ33,3 + Γ33 Γ03 − Γ33 Γ03 + Γ33 Γ13 − Γ33 Γ13 + Γ33 Γ23 − Γ33 Γ23 + Γ33 Γ33 − Γ33 Γ33

[

(

(

) ( Γ ) + (Γ

)(

) (

)

(

) (

)]

) ( Γ )+ (Γ

)] Γ )]

[

(

) (

) (

) (

)]

We are left with
1 0 1 1 1 1 2 1 3 R00 = −Γ00 ,1 + Γ01Γ00 − Γ00 Γ11 − Γ00Γ12 − Γ00Γ13 , 0 0 0 1 0 2 1 2 2 2 3 1 3 3 3 R11 = Γ10 ,1 + Γ10 Γ01 − Γ11Γ10 + Γ12 ,1 − Γ11Γ12 + Γ12Γ21 + Γ13,1 − Γ11Γ13 + Γ13Γ31 , 1 0 1 1 1 2 1 3 1 3 3 3 R22 = −Γ22 Γ10 − Γ22,1 − Γ22 Γ11 + Γ21Γ22 + Γ23, 2 − Γ22Γ13 + Γ23Γ32 , 1 0 1 1 1 3 1 2 1 2 3 2 R33 = −Γ33Γ10 − Γ33,1 − Γ33Γ11 + Γ31Γ33 − Γ33, 2 − Γ33Γ12 + Γ32 Γ33 .

These equations must equal zero, thus after substitution, we have:

 B′A′ A′′ A′A′ A′  1 R00 =  − + −  , 2 4A r B  4B 2 A′ A′′ A′B′ B′A R11 = − , + − − 4A 2 4B Br A′r B′r 1 R22 = − + −1, 2 AB 2 B 2 B B′r 1  2  A′r R33 =  − + − 1 sin θ = R22 sin 2 θ . 2 AB 2 B 2 B   
Equation 2 becomes:

(1)

(2) (3) (4)

A′2 A′′ A′B′ B′A B′A A′2 A′′ A′B′ 0=− . + − − ⇒ =− + − 4A 2 4B 4A 2 4B Br Br
This can be substituted into equation 1 to give:

B′A A′ B′ A′  B′A A′  1 0 = − −  ⇒ =− ⇒ =− . r B Br r B A  Br
This can also be written as:

Courtney James Mewton

Page 4

GR, Tensor Analysis & Geometry

GENERAL RELATIVITY, TENSOR ANALYSIS AND GEOMETRY

1 dB dA dB dA =− ⇔ =− ⇒ B = ⇒ AB = 1 , Bdr Adr B A A
upon solving the simple differential equation. We use this solution to simplify equation 3:

0=
We now integrate:

A′r A′r ′ + + A − 1 ⇔ 1 = A′r + A = A′r + Ar ′ = (Ar ) 2 2A

∫ dr = ∫ dr (Ar )dr ⇒ r + k = Ar ,
d
where k is an integration constant. The equation can be rearranged to find A:

A =1+
Since

k . r
−1

B = A −1 ,  k B = 1 +  . r 

The value of k is the last thing to obtain. In the next section on the approximation of Newtonian gravitation, g 00 = 1 + h00 . It can immediately be seen that the h00 is equivalent to k. In the Newtonian approximation, it is required that the Newtonian gravitational potential
2

V = 1 c 2 h00 . 2

Using the Newtonian potential

V = − GM r , this gives a value of k = − 2GM rc . By substituting A and B back into the original lineelement equation at the start of this section, we have the Schwarzchild solution:  2GM c 2 dτ 2 =  1 − rc 2   2 2  2GM  dr 2 − r 2 dθ 2 + sin 2 θdφ 2 . c dt − 1 − 2  rc   
−1

(

)

Utilising Geodesic Equation to Find GR Approximation of Newtonian Gravity
A particle travels through spacetime along a geodesic, given by the equation:
ν σ dx µ µ dx dx + Γνσ = 0. dτ dτ dτ 2

τ is the time experienced relative to the particle. The equation simply states that relative to a free particle, it experiences no net acceleration (though other objects appear to accelerate if a gravitational field is present). We wish to determine the motion of the particle relative to coordinate time, denoted by t. The equation would give the path of the particle in accordance to what other observers would see if they thought they were in a gravitational field. With the above said, the following equation can be immediately written, transforming from proper time to coordinate time:
ν σ  d 2t d 2xµ µ dx dx + Γνσ = 2  dτ dt dt dt 2 
2 µ  dt   dx .  2   dτ   dt  2 i  dt   dx  .  2   dτ   dt dx 0 dx k . We simplify the dt dt

First, we expand and consider its spatial components:
0 0 0 j k k  d 2t d 2 xi i dx dx i dx dx i dx dx + Γ jk + 2Γ0 k + Γ00 = dt dt dt dt dt dt  dτ 2 dt 2  0 j i dx dx = Γ0i k One of the Christoffel symbols has a coefficient of two since Γ j 0 dt dt

equation:

 d 2t d 2 xi dx j dx k dx k i + Γ ijk + 2Γ0i k c + c 2 Γ00 =  2  dτ dt dt dt dt 2 
Courtney James Mewton Page 5

2 i  dt   dx .  2   dτ   dt 

GR, Tensor Analysis & Geometry

GENERAL RELATIVITY, TENSOR ANALYSIS AND GEOMETRY

We assume that the gravitational field is quasi-static, i.e. that it doesn't change with respect to time. Therefore, any derivatives of the metric tensor with respect to time can be left out. Now we evaluate the connection coefficients:

1 iρ g iρ  ∂g ρj ∂g ρk ∂g jk   Γ = g Γρjk = + − ρ  . These derivatives are quite small, and can be neglected.1 2 2  ∂x k ∂x j ∂x    iρ  ∂hρ 0 ∂h ρk ∂h  g  ∂g ρ 0 ∂g ρk ∂g 0 k   k + 2Γ0i k = 2 − ρ  ≈ η iρ + h iρ  k + 0 − 0ρk  0  ∂x   ∂x 2  ∂x ∂x  ∂x ∂x    ∂hµν  ∂h0 ρ ∂h ρk ∂h  ∂h   ∂h ≈ η iρ + h iρ  k + 0 − 0ρk  ≈ −δ is  0ks − 0sk  on neglecting terms involving .  ∂x ∂x ∂x  ∂x  ∂x 0  ∂x   g iκ  ∂g κ 0 ∂g 0κ ∂g 00  δ iz ∂h00 i Γ00 = + − κ ≈ .  2  ∂x 0 2 ∂x z ∂x 0 ∂x 
i jk

(

)

(

)

Now we need to evaluate the RHS of the equation. We start by first looking at the following line element:

1 1 dx µ dxν dx µ dxν  dτ  1 c dτ = g µν dx dx ⇔   = 2 ( µν + hµν ) η = 2 ( + hµν ) . dt dt dt dt c c  dt 
2 2 2

µ

ν

Neglecting

terms involving the spatial components, which are small in comparison to the temporal components, we get:

dτ  dτ  12 = (1 + h00 ) ≈ (1 + 1 h00 ) .   = (1 + h00 ) ⇒ 2 dt  dt  dh d 2τ dh00 = = c 00 , so the RHS of our major equation becomes: Now 2 dt dt dx 0 dh00 2 2 i  i  c dx 0 dx i dh00 dx d t  dt  (1 − 12 h00 ) dx . ≈c 0   ≈  dt  dτ 2  dτ 2   1 + 1 h00 dt dt dx 2  
2

This is negligible since it involves temporal derivatives of the gravitational field. By plugging everything into our equation, we get:

∂h  dx k δ iz ∂h00 d 2 xi  ∂h − δ is  0ks − 0sk  + c2 =0. 2 ∂x z dt 2 ∂x  dt  ∂x
Through multiplying by mass m and rearranging the equation, we get:

∂h  dx k δ iz ∂h00 d 2 xi  ∂h m 2 = − mc 2 + mδ is  0ks − 0sk  . 2 ∂x z dt ∂x  dt  ∂x
The term on the left is the force that the particle appears to experience. The first term on the right is some kind of potential of the field, since its temporal component is involved. The last term, which involves perpendicular velocities, is indicative of some sort of Coriolis force. We are not interested in the Coriolis effects, so we shall assume that we are in a non-rotating frame, so we get:

δ iz ∂h00 d 2 xi = − mc 2 . 2 ∂x z dt 2 2 If we denote a potential by V = 1 c h00 , then the equation simply becomes F = − m∇V , or 2
m d 2 xi ∂V = −δ iz z . We want the metric tensor to be flat when there is no gravitational field present. The 2 dt ∂x
1

The metric tensor

g µν ≈ η µν + h µν , where η µν is the familiar metric tensor of Special Relativity, and

h µν are small terms which include the action of any gravitational fields which may be present, and are small in µν comparison to the η in weak gravitational fields, as opposed to the awesome sucking power of a black hole!
Courtney James Mewton Page 6 GR, Tensor Analysis & Geometry

GENERAL RELATIVITY, TENSOR ANALYSIS AND GEOMETRY

equation for the potential leads us to the expression

g 00 = η 00 + h00 = 1 + 2V c 2 . To finally get the actual

expression for the potential in terms of mass, we need to use the line element from the Schwarzchild solution. The temporal component gives V = − GM r . With this expression, we can easily obtain an approximation of the gravitational force:

F = − m∇V = − GMm r 2 . Field Equations in the Presence of Matter: The Poisson Approximation
Let us write the equation:

R µν − 1 g µν = κT µν , 2
or, more compactly as:

G µν = κT µν ,
where G is the Einstein tensor. As a test for General Relativity, at velocities which are small in comparison to the speed of light, there must be an approximation to Poisson’s equation: ∇ V = 4πGρ . To achieve this requires the weak field approximation by leaving out negligible terms in the Ricci tensor.2
2

R µν

G µν = κT µν − 1 g µν R = κT µν 2

g µν R µν − 1 g µν g µν R = κT µν g µν 2 R − 2 R = κT µν g µν ∴ R = −κT µν g µν
We substitute this back into our original equation:

R µν = κT µν + 1 g µν R = κT µν − 1 g µν κT µν g µν 2 2
We are approximating that the material energy tensor has a negligible value in for all µ, ν except when µ = ν = 0, so we get:

R 00 = κT 00 − 1 g 00κT 00 g 00 = 1 κT 00 . 2 2
We now make the Ricci tensor covariant:

g 00 g 00 R 00 = 1 κT 00 g 00 g 00 ⇔ R00 = 1 κT00 2 2
Weak field approximation.

Rµν ≈

1 2

(g

αα , µν

− gνα , µα − g µα ,να + g µν ,αα ) ≈ 1 g µν ,αα 2 1 2 ∇V c2

∴ R00 ≈ 1 g 00,αα ≈ 1 ∇ 2 g 00 = 2 2 ∴

1 2 ∇ V = 1 κT00 = 1 κρv0 v0 2 2 2 c ∇ 2V = 1 κρc 4 2

The particles are traveling at the travelling at the speed of light through time, so we get: This must equal Poisson’s equation, stated earlier This gives a value

κ=

8πG . c4

2

Note that this particular calculation would be shorter if we took the Einstein tensor and the material energy tensor to be covariant as opposed to contravariant, but due to the actual form of the material energy tensor, I prefer it to be contravariant.

Courtney James Mewton

Page 7

GR, Tensor Analysis & Geometry